Enhancing Latent Tuberculosis Infection Treatment Adherence with Mobile Health Intervention: A Quasi-Experimental Study - Rohitashwa Kumar; Manmohan Singhal; Ravishankar N; Abhijeet P Sinha; Ashwani Verma; Bhavna Kumar; KM Monirul Islam (National Journal of Community Medicine, 2024)
Introduction: While detecting active TB is central to public health efforts, modelling indicates that reducing latent TB through preventive therapy is crucial. Current regimens mitigate risk but are lengthy and have side effects, necessitating support for uninterrupted treatment. This paper presents the development and evaluation of a digital health platform designed to enhance adherence among LTBI patients.